Pembatalan Sertifikat Hak Milik Dibebani Hak Tanggungan (Putusan Mahkamah Agung Nomor 1138 K/Pdt/2012) - Prakasa, Fasatama; Apriani Zuhir, Mada; Adriansyah, Herman (Recital Review, 2020)
Certificate that is burdened with Rights of Liability with a case study based on Decision of the Supreme Court Num. 1138 K/Pdt/2012. This research is a normative legal research using legislative approach, conceptual approach, and philosophical approach. The type and legal materials obtained from primary, secondary, and legal materials,collected through library study, with deductive deduction techniques. The results of this study are, the judge’s consideration of the revocation of the Ownership Rights Certificate that is burdened with Rights of Liability based on Decision of the Supreme Court Num. 1138 K/Pdt/2012is that in the process of making a sale and purchase deed of land rights made by a Land Deed Officer(PPAT) is a legal defect due to engineered by Defendant 1 along with Defendant III (Notary/PPAT), and Defendant 1 did not have the authority to bind Rights of Liability assuranceof land rights object. Legal protection against separatist creditors as holders of Rights of Liability, namely the right to obtain their own authority to sell/execute assurance objects without waiting for a court decision. The supposed arrangement for the revocation of Ownership Rights Certificate burdened with Rights of Liability is to strengthen the value of authentic deeds such as the Deed of Rights of Liability that protects the rights of creditors in guaranteeing creditor rights in registering. The PPAT’s responsibility for the deed which is canceled based on the Regulation of the Land Deed Officer, namely compensation from the aggrieved party’s claims, administrative sanctions, and charged for criminal acts of letter forgery.